Linguistic analysis of trading agreements insights for plain writing in Philippine contracts - Tenedero, Pia Patricia P. (2015)
A Philippine bill has been put forward with the view to simplify legal documents, a timely initiative in the advent of the ASEAN Economic Community in 2015, which portends heightened importance of business contracts. In consonance with the global effort to apply plain writing, this paper examines four linguistic features of five online trading agreements. Using corpus stylistics and informed by principles of pragmatics and readability, the analysis confirms that the examined trading agreements possess the traditional legal form characterized by the use of impersonal noun references; modal verbs, particularly shall; legal archaisms; and long sentences. While the Plain Writing for Public Service Act of 2013 is pending ratification, it appears that stock broker companies in the Philippines have already begun with their efforts to simplify their consumer contracts. Benchmarking on USA Plain English Laws, the study also proposes some guidelines to make trading agreements objectively comprehensible to nonspecialist users.
Keywords: Legal documents; Writing